Study of The Influence of Excipients on The Quality Of "Simverin" Tablets - Kholida Mannanovna, Yunusova; Nargiza Bakhtiyarovna, Ilkhamova; Muhayyo Karimovna, Ismailova; Muattar Shukhrat qizi, Jaloliddinova; Abbaskhanovna, Azimova Nargizakhon (Journal of Neonatal Surgery, 2025)
In these studies, the effect of excipients on the pharmacotechnological properties of the recommended tablets was examined, as well as their influence in different ratios during the development of the recommended tablets. The impact of excipients with various chemical structures was studied to obtain the combined tablets "Simverin." In order to improve the technological process of manufacturing the recommended tablets, a comparative evaluation of the pharmacotechnological properties of the tablets was carried out using different excipients. The most well-known excipients used in the composition of pharmaceutical dosage forms available on the pharmaceutical market were selected for this study